Plasmid-Encoded AmpC (pAmpC) in Enterobacteriaceae: epidemiology of microorganisms and resistance markers - Cejas, Daniela (2012)
CMY-2ß-lactamase is an important cause ofß-lactam resistance in Enterobacteriaceae and constitutes the most widespread pAmpC. Although CMY-2 has been previously recognized in our region, the real prevalence and epidemiology of this resistance marker was uncertain. During August-October 2009, we conducted a multicenter, prospective study to determine pAmpC prevalence and to characterize CMY-2 producing Escherichia coli associated plasmids. Plasmid-encoded AmpC prevalence was 0.9 % in enterobacteria in this period, being CMY- 2 prevalent and to a lesser extent DHA. Molecular typing of CMY-2- producing Escherichia coli isolates showed several lineages. Moreover, replicon typing of cmy-2- containing plasmids displayed a broad diversity in Inc/cmy- 2 links. Therefore, association of cmy-2 with specific transposon elements may be responsible for the spread of this resistance marker in Enterobacteriaceae.